Penerapan Konsep Neo Vernakular dan Kebutuhan Pengguna pada Desain Terminal Bus Tipe A di Jepara - Atiek Untarti (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
Jepara Terminal is a bus terminal that was developed as a type A bus terminal node because the terminal is located in the area of ​​the Urban Local Activity Center system. To be able to meet the growth of city functions, it is necessary to increase the existing terminal in accordance with the functions and needs of the user community. With a local architectural approach in modern architecture, the design of the Type A Terminal building in Jepara was designed with the Neo Vernacular concept. The method used is through literature study to decide the concept of locality. Meanwhile, in determining the space program according to the user's needs, an on-line application is carried out via a cellular phone. The results from a literature review of Neo Vernacular architecture and space requirements in the Type A Terminal building design in Jepara are outlined in a schematic design architecture with the Neo Vernacular concept